Cultural Capital and its Impact on the Career Experiences of African American Managers - Trammell L. Bristol (Adult Education Research Conference, 2007)
This paper summarizes the result of a qualitative study where the purpose was to explore the factors which facilitated the career development of African American managers. Based on these findings, recommendations for practice are suggested in HRD and adult education.